Jumlah Populasi Imago Sitophilus oryzaeÂ L. dan Intensitas Kerusakan pada Beberapa Jenis Beras Asal Kecamatan Mauponggo, Kabupaten Nagekeo, Provinsi Nusa Tenggara TimurÂ - Veronika Munde; Titik Sri Harini; Petronella S. Nenotek; Zainal Abidin; Yosep Seran Mau (Postgraduate, University of Mataram, 2023)
This study aimed to determine the S. oryzae imago number and the level of damage intensity it caused on grains of several rice varieties in Mauponggo District, Nagekeo Regency. The study was conducted at the Pest Laboratory of the Faculty of Agriculture, Nusa Cendana University. The study was laid out in a completely randomized design consisting of five rice varieties as treatments, each was four replicates. A rice grain of 100 grams was put into a plastic jar and infested with a uniform five pairs of S. oryzae. Observed variables included grain water content, number of S. oryzae imago and the percentage of grain weight loss as a measure of damage intensity. Data were subjected to analysis of variance, followed by an Honest Significant Post hoc test at a 0.05 % significance level. The study results showed significant differences among tested rice varieties in both imago populations as well as the level of grain weight loss. IR 64 variety showed the lowest number of imago of S. oryzae and also the lowest grain weight loss while local red and black rice were the highest in both the number of imago and grain weight loss at eight weeks after S. oryzae infestation.